The Effectiveness of Mindfulness-Based Stress Intervention on Grief Experience and Social Isolation Among Martyrs' Spouses - Keykha, Zeynab; Arab, Ali; Karbalai Herofteh, Fatemeh Soghra (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to examine the effectiveness of a mindfulness-based stress intervention in reducing grief experience and social isolation among martyrs' spouses.Methods and Materials: This quasi-experimental study employed a pretest-posttest design with a control group. The statistical population included martyrs' spouses in the city of Zahedan, from which 40 individuals were purposefully selected and randomly assigned to an experimental group (20 individuals) and a control group (20 individuals). Data collection tools included the Grief Experience Questionnaire by Bart and Scott (1998) and the Social Isolation Scale by Chalabi and Amir-Kafi (2004). Data were analyzed using analysis of covariance (ANCOVA).Findings: The results indicated that the mindfulness-based stress intervention significantly reduced the scores of grief experience and social isolation among martyrs' spouses (p < 0.001). Specifically, the mean grief experience score in the experimental group decreased from 111.5 to 47.4, and the mean social isolation score decreased from 92.45 to 34.8.Conclusion: The mindfulness-based stress intervention is an effective method for reducing grief and social isolation in martyrs' spouses. The application of this approach can help improve mental health and enhance the quality of life for this group.